ANALISIS TANGGUNG JAWAB PELAKU USAHA RESTORAN KOPI PENG DALAM MEMBERIKAN UPAH MINIMUM PROVINSI (UMP) KEPADA KARYAWAN DI KOTA PONTIANAK - NIM. A1011221025, IVAN HALIM (Fakultas Hukum Universitas Tanjungpura, 2026)
Wages constitute a normative right of workers that employers are obligated to fulfill as a consequence of an employment relationship. The government has established a minimum protection standard through the Provincial Minimum Wage (UMP) policy, which for West Kalimantan in 2026 was set at IDR 3,205,220 pursuant to the Decree of the Governor of West Kalimantan Number 1355/NAKERTRAN/2025. However, in practice, some business owners have not fully complied with this regulation, one of which is the Kopi Peng Restaurant in Pontianak City. This study aims to analyze the accountability of the Kopi Peng Restaurant owner regarding employee wages, and to examine the forms of legal responsibility that arise if the business owner is proven to have failed to pay wages in accordance with the UMP provisions. This research employs a normative-empirical legal research method (socio-legal research) with a descriptive-analytical approach. Primary data were collected through interviews with 1 (one) restaurant manager and 5 (five) employees of Kopi Peng Ayani Pontianak, supported by direct observation. Secondary data were obtained from primary legal sources in the form of legislation, as well as secondary legal materials including books, journals, and relevant legal literature. Data were analyzed qualitatively using a descriptive-analytical method. The research results reveal two main findings. First, the wages received by Kopi Peng Restaurant employees ranged from IDR 1,300,000 to IDR 2,912,000 per month, which is IDR 293,220 to IDR 1,905,220 below the West Kalimantan UMP for 2026. Contributing factors include the company's financial constraints, the absence of written employment agreements, employees' limited legal awareness, and weak supervision by labor authorities. This situation indicates that preventive legal protection has not been effectively implemented. Second, business owners who are proven not to have paid wages in accordance with the UMP may be subject to three forms of legal responsibility: (a) administrative responsibility in the form of written warnings up to suspension of business activities; (b) civil responsibility in the form of an obligation to pay wage shortfalls, which can be pursued through bipartite mechanisms, mediation, or the Industrial Relations Court; and (c) criminal responsibility under Article 185 in conjunction with Article 90 paragraph (1) of Law Number 13 of 2003 on Manpower, with a threat of imprisonment of 1 to 4 years and/or a fine of IDR 100,000,000 to IDR 400,000,000. Keywords: Legal Responsibility, Business Owner, Provincial Minimum Wage, Legal Protection, Labor Law. Upah merupakan hak normatif pekerja yang wajib dipenuhi oleh pengusaha sebagai konsekuensi adanya hubungan kerja. Negara telah menetapkan standar perlindungan minimum melalui kebijakan Upah Minimum Provinsi (UMP), yang untuk Kalimantan Barat tahun 2026 ditetapkan sebesar Rp3.205.220 berdasarkan Keputusan Gubernur Kalimantan Barat Nomor 1355/NAKERTRAN/2025. Namun dalam praktiknya, masih terdapat pelaku usaha yang belum sepenuhnya mematuhi ketentuan tersebut, salah satunya Restoran Kopi Peng di Kota Pontianak. Penelitian ini bertujuan untuk menganalisis pertanggungjawaban pelaku usaha Restoran Kopi Peng terhadap upah karyawannya, serta mengkaji bentuk tanggung jawab hukum yang timbul apabila pelaku usaha terbukti tidak membayar upah sesuai ketentuan UMP. Penelitian ini menggunakan metode penelitian hukum normatif empiris (socio-legal research) yang bersifat deskriptif-analitis. Data primer diperoleh melalui wawancara dengan 1 (satu) orang pimpinan dan 5 (lima) orang karyawan Restoran Kopi Peng Ayani Pontianak, didukung dengan observasi langsung. Data sekunder diperoleh dari bahan hukum primer berupa peraturan perundang-undangan, serta bahan hukum sekunder berupa buku, jurnal, dan literatur hukum yang relevan. Data dianalisis secara kualitatif menggunakan pendekatan deskriptif-analitis. Hasil penelitian menunjukkan dua temuan utama. Pertama, upah yang diterima karyawan Restoran Kopi Peng berkisar antara Rp1.300.000 hingga Rp2.912.000 per bulan, atau lebih rendah Rp293.220 hingga Rp1.905.220 di bawah ketentuan UMP Kalimantan Barat tahun 2026. Penyebabnya meliputi keterbatasan finansial perusahaan, tidak adanya perjanjian kerja tertulis, rendahnya pemahaman hukum karyawan, dan lemahnya pengawasan instansi ketenagakerjaan. Kondisi ini menunjukkan bahwa perlindungan hukum preventif belum berjalan efektif. Kedua, pelaku usaha yang terbukti tidak membayar upah sesuai UMP dapat dikenai tiga bentuk tanggung jawab hukum: (a) tanggung jawab administratif berupa teguran tertulis hingga penghentian kegiatan usaha; (b) tanggung jawab perdata berupa kewajiban membayar kekurangan upah yang dapat ditempuh melalui mekanisme bipartit, mediasi, atau Pengadilan Hubungan Industrial; dan (c) tanggung jawab pidana berdasarkan Pasal 185 juncto Pasal 90 ayat (1) Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, dengan ancaman pidana penjara 1 hingga 4 tahun dan/atau denda Rp100.000.000 hingga Rp400.000.000. Kata Kunci: Tanggung Jawab Hukum, Pelaku Usaha, Upah Minimum Provinsi, Perlindungan Hukum, Ketenagakerjaan.